一种新型的仿生步行机构及其运动仿真 - 汪永明; 余晓流; 汪丽芳; 汤文成 (Jixie chuandong)
Imitating animals asymmetric motion,a new-style bionics walking mechanism is designed by using two tandem planetary gear trains,which is composed of one first swiveling arm,one second swiveling arm,two striding rods and walking bracket,etc.In which,the first and second swiveling arm are the planet carriers（also as gearbox casings） of the planetary gear trains.On the basis of interference analysis,non-interference condition of the mechanism is given.Based on motion simulation in COSMOS Motion software,the motion trail curves of joints of the bionics walking mechanism are obtained,and the fluctuation is also analyzed.The simalations show that the fluctuation of the bionics walking mechanism is small and meets the mobility of exploration.